THE INFLUENCE OF LIQUIDITY, SOLVABILITY, PROFITABILITY, AND COMPANY SIZE ON AUDIT DELAY (An Empirical Study of Listed Property, Real Estate, and Building Construction Companies on the Indonesia Stock Exchange) - Audi Rahmawati Pamungkas (Jurnal Ilmiah Mahasiswa FEB, 2019)
The aim of this research is to determine the influence of liquidity, solvability, profitability, and company size on audit delay in property, real estate, and building construction companies on the Indonesia Stock Exchange. The utilized sampling technique in this research was purposive sampling. The number of population in this research is 87 and the number of samples was 38. The utilized analysis technique in this research was multiple regression analysis. The results of this research showed that two out of the four variables do influence audit delay. The two variables are solvability and profitability.Keywords: audit delay, liquidity, solvability, profitability, and company size